A measurement of ∆Γs - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Cocha Toapaxi, Carlos; De Cian, Michel; Frau, Giulia; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Langenbruch, Christoph; et al. (Journal of high energy physics, 2024)
Using a dataset corresponding to 9 fb−1 of integrated luminosity collected with the LHCb detector between 2011 and 2018 in proton-proton collisions, the decay-time distributions of the decay modes B0s → J/ψη′ and B0s → J/ψπ+π− are studied. The decay-width difference between the light and heavy mass eigenstates of the B0s meson is measured to be ∆Γs = 0.087 ± 0.012 ± 0.009 ps−1, where the first uncertainty is statistical and the second systematic
LHCb Collaboration: R. Aaij, S. Bachmann, L. Carus, R. Caspary, C.E. Cocha Toapaxi, M. De Cian, G. Frau, F. Glaser, P.A. Günther, X. Han, S. Hansmann-Menzemer, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, S. Roy, M. Ruiz Diaz, G. Tuci, L.H. Ueckert, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, Y. Zhao, A. Zhelezov [und 1077 weitere]
Im Titel ist das s tiefgestellt
Gesehen am 05.05.2025